2008
DOI: 10.1080/13803390701416197
|View full text |Cite
|
Sign up to set email alerts
|

Switching and clustering in verbal fluency tasks throughout childhood

Abstract: An analysis of switching and clustering in fluency tasks was conducted on data from 180 Hebrew speakers aged 8-29. On the phonemic task, total output, number of switches, and number of clusters differed significantly across age groups and increased with age, whereas mean cluster size did not. On the semantic task, all measures increased with age. No differences were found between adolescents and adults on the phonemic variables, but adults provided more switches on the semantic task than did adolescents. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

19
88
1
17

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(145 citation statements)
references
References 35 publications
19
88
1
17
Order By: Relevance
“…Studies with primary school students (6-15 years old) 18,23 concluded that around eight or nine years the ability of clustering and knowledge of lexical organization is already established closely to adulthood, while the number of correct answers already consolidated at 14 years old, although the vocabulary follow its expansion during adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with primary school students (6-15 years old) 18,23 concluded that around eight or nine years the ability of clustering and knowledge of lexical organization is already established closely to adulthood, while the number of correct answers already consolidated at 14 years old, although the vocabulary follow its expansion during adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found in young adults without conditions, total words recalled that varied between 14.0 and 26.2 on average in the semantic test, and 9.5 and 15.1 in phonological test; already for the average cluster size, the values range between 0.75 and 1.7 for semantics, and phonological between 0.24 and 1.4. The number of switches varies in studies between 7.0 and 11.6 for the group "animals" and between 7.9 and 10.55 for letters 12,[14][15][16][17][18] . Regarding the comparative performance of the two tests and the factors determining the results, there is greater agreement in the literature, and in this study has obtained similar data to studies cited, even analysing itself a different population.…”
Section: Discussionmentioning
confidence: 99%
“…Em grupos clínicos com comprometimento das funções executivas na infância (fenilcetonúria e transtorno do défi-cit de atenção e hiperatividade), a redução da flexibilidade na busca de palavras, evidenciada pelo escore de transição, mostrou-se determinante para o número total de palavras produzidas (Banerjee, Grange, Steiner, & White, 2011;Gonçalves, 2015). Já o tamanho médio de agrupamento se correlacionou às medidas de vocabulário e ao funcionamento dos lobos temporais (Kavé, Kigel, & Kochva, 2008).…”
unclassified
“…Isso tem sido interpretado como um papel particularmente importante da flexibilidade das estraté-gias de busca, quando esta é feita com base em uma categoria semântica (Sauzéon et al, 2004). Já para o método valor bruto, o número de transições contribui de modo significativo para a produção de palavras tanto na FVF como na FVS (Kavé et al, 2008) e sugere que a flexibilidade também determina a busca de palavras por categoria fonológica. As divergências entre as interpretações decorrentes do uso de métodos de pontuação variados para escores estratégicos podem limitar sua validade enquanto medida de funções executivas e habilidades linguísticas (Koren et al, 2005), uma vez que cada método de pontuação explica o desenvolvimento cognitivo infantil de forma diferente.…”
unclassified
See 1 more Smart Citation